Algebra Structure of Operator-Valued Riesz Means. (18th May 2014) - Miana, Pedro J.
Abstract : We characterize operator-valued Riesz means via an algebraic law of composition and establish their functional calculus accordingly. With this aim, we give a new integral expression of the Leibniz derivation rule for smooth functions.